Analisis Penerapan Kurikulum Merdeka pada Sekolah Penggerak dalam Mewujudkan Profil Pelajar Pancasila - Sinta Nuryuliani; Damanhuri Damanhuri; Wardatul Ilmiah (JURNAL PENA EDUKASI, 2024)
Abstract: This research was carried out because several problems were still found in implementing the independent curriculum in driving schools, so the realization of students as Pancasila student profiles was hampered. This research aimed to describe how the independent curriculum at driving schools contributes to realizing the Pancasila student profile and the supporting and inhibiting factors in its implementation at SMA Negeri 16 Pandeglang. The method used in this research is qualitative. The results of this research show that the independent curriculum has been implemented in driving schools to realize the Pancasila student profile, referring to the School Operational Curriculum (KOS), and the results can be seen in several characteristics of class XI and XII students, such as (1) independence; (2) creativity; and (3) cooperation. There are obstacles experienced, starting with the low quality of students, facilities, and parental support. The independent curriculum at the driving school at SMA Negeri 16 Pandeglang has been well implemented, starting with planning, implementation, results, and evaluation. There are supporting and inhibiting factors internally and externally, and the school provides solutions related to the obstacles faced in its implementation.Keywords: independent curriculum; school mover; P5Abstrak: Penelitian ini dilakukan karena masih ditemukan beberapa permasalahan dalam penerapan kurikulum merdeka pada sekolah penggerak, sehingga perwujudan peserta didik sebagai profil pelajar Pancasila menjadi terhambat. Penelitian ini dilakukan dengan tujuan untuk mendeskripsikan bagaimana penerapan kurikulum merdeka pada sekolah penggerak dalam mewujudkan profil pelajar Pancasila, apa saja faktor pendukung dan faktor pemghambat dalam penerapnnya di SMA Negeri 16 Pandeglang. Metode yang digunakan dalam penelitian ini adlah kualitatif. Hasil penelitian ini menunjukan sudah diterapkannya kurikulum merdeka pada sekolah penggerak dalam mewujudkan profil pelajar Pancasila mengacu pada Kurikilum Operasional Sekolah (KOS) dan hasilnya terlihat pada beberapa karakter peserta didik kelas XI dan XII seperti: (1) mandiri, (2) kreatif dan (3) gotong royong, serta terdapat hambatan yang dialami mulai dari rendahnya kualitas peserta didik, fasilitas dan dukungan orang tua. Penera-pan kurikulum merdeka pada sekolah penggerak di SMA Negeri 16 Pandeglang sudah diterap-kan dengan baik mulai dari perencanaan, pelaksanaan,hasil dan evaluasi, adanya faktor pen-dukung dan penghambat secara internal dan eksternal serta sekolah memberikan solusi terkait hambatan yang dihadapai dalam penerapannya.Kata kunci: kurikulum merdeka; sekolah penggerak; P5